Gestão da qualidade em cadeias de suprimentos do segmento de motores de automóveis - Zagha, Roberta Resende (2009)
This work seeks to identify and analyze the quality management forms adopted by two engine assemblers and by nine of their first and second tier suppliers, discussing the relationships between the quality management form implemented by each assembler and the ones implemented by its suppliers in each supply chain studied. In a second moment, this work compares the two sets of quality management forms adopted in those two supply chains. Three hypotheses orient this research: the two engine assemblers adopt different quality management forms; the suppliers of those engine assemblers adopt different quality management forms as well; the two sets of quality management forms adopted in those supply chains are different, since the distinct quality management forms implemented by the assemblers and by their respective suppliers are conditioned by different supply chain structures and relationships. This work is accomplished through some literature revisions on the topics associated to the mentioned subject and secondly through a field research that involves case studies carried out in two supply chains. These two supply chains have different configurations: they are headed by two engine assemblers that present distinct levels of vertical integration and have different types of relationships with their respective suppliers. In each one of the analyzed companies two engine assemblers and nine suppliers (from the first and the second tiers) some semi-structured interviews were realized. The results indicate that the quality management forms implemented by the two engine assemblers are very similar. They indicate as well that the adoption of the conception main principles and guidelines of the Total Quality Management by all suppliers assures certain resemblance amongst the quality management forms implemented by them. But there are indications that the adopted forms by the suppliers are different, being the most sophisticated practices implemented by the multinational suppliers. It is observed an association between the differences in the supply chain structures and relationships and the differences in the two sets of quality management forms adopted (in the two chains). The supply chain in that the assembler has a higher degree of outsourcing and a bigger proportion (and absolute number) of smaller and national capital suppliers, with the goal of having cost advantages (with lower prices and lower transport costs), must, in compensation, spend bigger effort to guarantee the quality of the components it acquires. The chains characterized by engine assemblers having fewer suppliers are usually noticeable by long term relationships, with a greater number of large-sized suppliers, more technologically capable (generally multinationals companies certified according to quality standards), must make a relatively bigger effort to negotiate with suppliers, but a much lower effort to develop them.